Correlation of Electrolyte Volume and Electrochemical Performance in Lithium-Ion Pouch Cells with Graphite Anodes and NMC532 Cathodes. Issue 6 (7th April 2017) - An, Seong Jin; Li, Jianlin; Mohanty, Debasish; Daniel, Claus; Polzin, Bryant J.; Croy, Jason R.; E. Trask, Stephen; Wood, David L.
Abstract : The work herein reports on studies aimed at exploring the correlation between electrolyte volume and electrochemical performance of full cell, pouch-cells consisting of graphite/ Li1.02 Ni0.50 Mn0.29 Co0.19 O2 (NMC-532) as the electrodes and 1.2 M LiPF6 in ethylene carbonate:ethylmethyl carbonate (EC:EMC) as the electrolyte. It is demonstrated that a minimum electrolyte volume factor of 1.9 times the total pore volume of cell components (cathode, anode, and separator) is needed for long-term cyclability and low impedance. Less electrolyte results in an increase of the measured ohmic resistances. Increased resistance ratios for charge transfer and passivation layers at cathode, relative to initial values, were 1.5–2.0 after 100 cycles. At the cathode, the resistance from charge transfer was 2–3 times higher than for passivation layers. Differential voltage analysis showed that anodes were less delithiated after discharging as the cells were cycled.